2011
DOI: 10.4314/evj.v15i2.67694
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of gastrointestinal helminthiasis of small ruminants in selected sites of North Gondar zone, Northwest Ethiopia

Abstract: A cross-sectional study was conducted to determine the prevalence and risk factors associated with small ruminant helminthiasis in north Gondar zone, northwest Ethiopia from November-January, 2008. A total of 558 small ruminants (458 sheep and 100 goats) were examined using standard parasitological procedure. The study revealed that the overall prevalence of helminthiasis was 47.67%. The species level prevalence of helminthiasis was 46.07% and 55% in sheep and goats respectively. Strongyles were the most preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
46
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 17 publications
28
46
6
1
Order By: Relevance
“…This finding agrees with the reports of other researchers; Regassa et al [6] and Dagnachew et al [13] who reported 54.1% and 47.67% from Ethiopia, respectively. However, it is relatively lower than 79.09% [14], 76.3% [15] 59.89% [16] and 68.1% [17] reports from different parts of the country.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding agrees with the reports of other researchers; Regassa et al [6] and Dagnachew et al [13] who reported 54.1% and 47.67% from Ethiopia, respectively. However, it is relatively lower than 79.09% [14], 76.3% [15] 59.89% [16] and 68.1% [17] reports from different parts of the country.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in agreement with reports from Gambia and Kenya that indicated GIT helminthes affect both ages equally [24,28] and there are instances where younger animals were reported with high rate of parasitic infection [16]. In contrary, other authors have documented that nematode infection is higher in adult and old animals than the younger [11,13,29]. However, with this study we ascribed the absence of significant difference in parasites infection between ages of animals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Goats were also infected with a wider spectrum of GI parasites. This contradicts some previous studies that found a lower prevalence in goats (Kanyari et al, 2009;Khan et al, 2010;Abebe et al, 2011), but is in agreement with a number of other studies, which also reported higher parasite prevalence in goats (Regassa et al, 2006;Nwosu et al, 2007;Gadahi et al, 2009;Dagnachew et al, 2011). Hoste et al (2008) suggested that goats do not develop resistance as efficiently as sheep and this may be an explanation for our findings.…”
Section: Discussionsupporting
confidence: 65%
“…This is still very low compared to the prevalence reported in other countries: 82% in Togo (Bonfoh et al, 1995); 94% in Middle Guinea (Barry et al, 2002) and 60% in Eastern Ethiopia (Sissay, 2007). Lower prevalence also been reported elsewhere (Tariq et al, 2010;Dagnachew et al, 2011;Qamar et al, 2011).…”
Section: Epg Levels Of H Contortus and Anaemic Conditionsupporting
confidence: 62%